FEMINISME DALAM MAJALAH PEREMPUAN - Helen Diana Vida (Sociae Polites, 2011)
AbstractMass media, as agents of culture, reflects the general condition of society. Among theexisting mass media, there are some that are closely linked to specific segments, forexample, women’s magazines. Women’s magazines in Indonesian contains the value offeminism and give affect to Indonesian women’s, they requires not only equality in genderbut also independence in their live.Keywords : Women Magazine, Feminism